(untitled) (Czech Journal of International Relations, 2006)
This article first disputes the traditional view of Realist School of international relations as inherently positivistic, and second presents a reaction to the polemic taking its course in pages of this journal between Marek Loužek and Petr Drulák. In the first part, those aspects of the work of E. H. Carr and Hans Morgenthau that challenge their placing in the positivist camp are presented. In the second part, these remarks are used as a critique of Marek Loužek’s schematic division of theories of international relations as between normativist idealism and positivist realism.